Final answer:
The equation -5 - 2(3x - 4) = 21 is solved by distributing the -2, combining like terms, and then isolating and solving for x, resulting in x equaling -3.
Step-by-step explanation:
To solve the equation -5 - 2(3x - 4) = 21, we need to perform operations step by step. First, we distribute the -2 across the parenthesis:
- -2 × 3x = -6x
- -2 × -4 = +8
Now the equation looks like this: -5 - 6x + 8 = 21.
Next, we combine like terms which are the constants -5 and +8:
The equation now simplifies to -6x + 3 = 21. We then isolate the term containing x by subtracting 3 from both sides:
- -6x + 3 - 3 = 21 - 3
- -6x = 18
Finally, to find the value of x, we divide both sides by -6:
Thus, the solution to the equation is x = -3.